Pengaruh Struktur Corporate Governance Terhadap Cost of Equity Capital - Rahmawati, Novia (Jurnal Ekonomi, 2009)
The purpose of this research is to provide empirical evidence about the impact of corporate governance's structure ti the cost of equity capital. Corporate governance's structures that used in this research consist of independent commissioner, audit committee, boards of directors, managerial and institutional ownership. Research sample are companies that listed in Jakarta Stock Exchange. Cross-sectional is used in this research with the period of observation is 2003. Method that used in testing hypothhesis is multiple Regression. Result of the test shows only one of five variables that have been tested, audit committee, have a negative significant impact to the Cost of Equity Capital. Means that Cost of Equity Capital in companies with audit commitee, can be lower than companies without audit committe.